2018
DOI: 10.1002/jbm.b.34251
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics release from cement spacers used for two‐stage treatment of implant‐associated infections after total joint arthroplasty

Abstract: Two‐stage revision arthroplasty is the treatment of choice for periprosthetic infection, a serious complication after knee or hip arthroplasty. Our prospective clinical trial aimed to investigate the concentrations of gentamicin and vancomycin in wound exudate and tissue in two‐stage revision arthroplasty. Wound exudate and periprosthetic membrane samples were collected from 18 patients (10 hip and eight knee patients), who were due for two‐stage treatment after a periprosthetic joint infection. Samples were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Periprosthetic joint infection (PJI) following total knee arthroplasty (TKA) has been one of the most serious and challenging complications. 1 Dale et al 2 reported that the incidence of PJI following TKA ranged from 0.5% to 2.0%. With the population aging, the incidence of TKA is growing rapidly and as a result, the number of PJI cases is also increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Periprosthetic joint infection (PJI) following total knee arthroplasty (TKA) has been one of the most serious and challenging complications. 1 Dale et al 2 reported that the incidence of PJI following TKA ranged from 0.5% to 2.0%. With the population aging, the incidence of TKA is growing rapidly and as a result, the number of PJI cases is also increasing.…”
Section: Introductionmentioning
confidence: 99%
“…In our experience, the advantages of custom-made spacers included retention of limb length and lateral offset, both of which made it easier to perform further revisional surgery[ 8 ]. Moreover, custom-made spacers also allow the treating surgeon to control the type and dosage of antibiotics[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 28% of the patients require repeated debridement due to infection recrudescence caused by MRSA. 14 Although up to 4 g of vancomycin can be added to 40 g cement powder when generating an antibiotic spacer, according to some clinical reports 15 , 16 and reviews, 17 , 18 less than 5% of the total vancomycin has been shown to be released from cement spacer, 19 , 20 and an effective vancomycin concentration was only detected during the first few days after spacer implantation. 21 , 22 Thus, the traditional approach of combining systemic vancomycin with an ALCS does not appear to be an optimal approach for achieving MBECs, due to the limited spacer antibiotic loading and release.…”
Section: Introductionmentioning
confidence: 99%